Acculturation In The Sugar Factory As a Tourist Destination (Ethnography Study At The Rejo Agung Baru Sugar Factory, Madiun, East Java, Indonesia). Issue 1 (May 2021) - Hayati, A; Faqih, M; Hartono, Y; Soebijantoro
Abstract: This research aims to reveal the potential of the Buka Giling traditions (a kind of traditional celebration in the open mill season) as a tourist destination place. The study used ethnographic methods. Data was obtained through observatory participant's technique, in-depth interview, and document analysis. Data that has been collected is analyzed by interactive analysis. The results show that historically the Buka Giling traditions in the Rejo Agung Baru Sugar Factory had been going since the factory was built during the Dutch colonial period in the early 19th century; culturally, it was acculturation among Javanese and Islamic culture. Its traditions were having potential as tourist destination places, such as cultural art performance, social activities, historical and architectural building.